Simulation of horizontal injection wells in Managed Aquifer Recharge facilities using the conduit flow process (CFP) code for MODFLOW-2005. (February 2022) - Perdikaki, Martha; Pouliaris, Christos; Makropoulos, Christos; Kallioras, Andreas
Abstract: Groundwater management of coastal aquifers is a scientific and engineering challenge, as coastal aquifer systems are hydrogeologic features that are hydraulically connected with the sea while at the same time are stressed with extensive abstraction practices for irrigation. To remedy this, Managed Aquifer Recharge -MAR- is proved to be a sound and effective technology that is able to fill the gap between groundwater supply and demand. Essential part of this procedure is reliable groundwater modeling that simulates effectively all involved hydrologic processes in order to be able to predict the response of the system under different natural or artificially induced conditions. This paper describes the application of a modeling tool, for the simulation of the relative hydrologic processes between the open filter pipe of the injection well and the surrounding aquifer material with the finite difference method. More specifically, a MAR pilot setup with a horizontal direction injection well was simulated with the Conduit Flow Process (CFP) of MODFLOW-2005 code. To investigate further the applicability of CFP code, the HDDW was conceptualized with the simpler MODFLOW WEL package and the results of the two models were compared. For the two models, sensitivity analysis was conducted using UCODE_2014. Both models were calibrated successfully as the simulated values showed an acceptable fit to the observed data. The main difference between the two packages was observed in the rise of groundwater level along the horizontal well. To this end, it was indicated that CFP offered a more realistic representation of the horizontal well pipe. Graphical abstract: Model conceptualization of the MODFLOW-CFP application for HDDW injection well simulation. Image 1 Highlights: Simulation of water injection via a Horizontal Directional Drilled Well with the Conduit Flow Process (CFP) for MODFLOW-2005. Application of CFP Mode 1, incorporating flow within the aquifer (MODFLOW-2005), flow in conduits and exchange fluxes. Most influential parameters are associated with the aquifer properties, rather than the conduit parameters. Conduit parameter values (conduit wall conductance, lower and upper Re number) had lower impact on the results of the model. Hydraulic conductivity of the recharged aquifer and GHB conductance proved of ample importance for the simulation.